Perencanaan Jadwal Induk Produksi Komponen Band Komp Battery di PT. Mada Wikri Tunggal - Aldi Raihan Rusnadi; Dene Herwanto (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
PT. Mada Wikri Tunggal is a company engaged in the automotive industry which produces small components in motor parts. A common problem experienced by each production company is the planning for the amount of production that must be in accordance with the production capacity coupled with fluctuating demand. So that companies can make orders according to capacity and also the time required for a Master Production Schedule. The method used is the changing labor method. Because this method is very suitable for companies that experience fluctuating demand. The results obtained are that the company can meet the existing demand for the period January to December 2021 as many as 48507 units. The Regular Time fare in 12 periods / 1 year is Rp. 242,685,000. The Hiring fee in 1 year is Rp. 16,000,000. The Lay Off fee in 1 year is Rp. 20,000,000. And the cost of Under Time for 1 year is Rp. 1,750,000. So the total production cost of PT. Mada Wikri Tunggal of Rp. 280,435,000.